Anti-HBsAg IgY polyclonal antibodies potential as capture antibody for HBsAg detection kit development - A'yun, Ramadhani Qurrota; Hakim, Meutia Diva; Giri-Rachman , Ernawati Arifin; Tan, Marselina; Niloperbowo, Wardono (Institut Teknologi Bandung, 2024)
Hepatitis B, affecting about 296 million globally, is a significant concern, with Indonesia ranking second in Southeast Asia for case numbers. The disease's latent initial phase, devoid of early symptoms upon hepatitis B virus (HBV) infection, highlights the demand for precise diagnostics. This research aimed to develop anti-HBsAg polyclonal antibodies (pAb) for application as capture agents within a sandwich enzyme-linked immunosorbent assay (ELISA). Chicken egg-derived IgY antibodies have advantages over mammalian ones due to simpler extraction and higher yield. In a study involving 21-week-old chickens, four intramuscular injections of 500 µg HBsAg antigen in Freund's adjuvant were administered at two-week intervals. Eggs as IgY source were collected daily and then IgY was isolated from eggyolk using polyethylene glycol (PEG) precipitation. The Bradford method was used to measure the total protein concentration, while the existence of IgY and pAb specific IgY against Anti-HBsAg was verified through SDS-PAGE and sandwich ELISA using HRP as a reporter, respectively. The resulting SDS-PAGE showed two distinct IgY bands: a 68 kDa heavy chain and a 23 kDa light chain. Using these anti-HBsAg IgY antibodies as capturing agents, the slightly elevation of IgY pAb against HBsAg level has been identified within the second week following the initial immunization. Subsequently, from the third to the eighth week, antibody levels escalated significantly, ranging from 2 to 13-fold higher than those observed in the second week. These findings suggest the potential use of IgY pAb as effective capture antibodies in sandwich ELISA for HBsAg antigen detection.